(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the stress factors that arise during driving and the effective methods for managing them. Stress directly affects the driver’s attention, reaction speed, and decision-making ability. Therefore, maintaining psychological stability and developing a culture of safe driving are essential aspects of professional driving competence. The paper analyzes breathing exercises, autogenic training, cognitive regulation, and mindful driving practices as techniques for stress reduction.